“The Pistol Plan” As a Crime Against Humanity Against Members of the National Army (2019)
In Colombia, during the most prolonged armed conflict in the Western Hemisphere, members of the Colombian National Army were executed through insulting practices (“executions”in insurgent terms) by groups outside the law, taking advantage of special circumstances such as helplessness, surprise or administrative situations, —e. g. allowances, breaks or transfers—. That criminal behaviour, which has been defined as a “pistol plan” (Plan Pistola), could constitute, in accordance with the international precedent and internal developments, crimes against humanity in the form of aggravated homicide (murder), by distancing itself from the descriptions of international humanitarian law. Indirect victims of the pistol plan in a transitional justice have the right to know the whole truth about how their relatives were executed, as well as to know from the perpetrators what were the policies and criminal orders in their organized groups for that these serious events happened.